Forager-traders in south and southeast Asia : long-term histories - Morrison, Kathleen D.; Junker, Laura Lee, 1958- (Cambridge University Press, 2002)
In both South and Southeast Asia, many upland groups make a living through various combinations of foraging and hunting. This book uses a series of detailed comparative case-studies to re-evaluate forager-trader groups and place them within the surrounding political, economic and social worlds of South and Southeast Asia.